The effect of self-management program on perceived social support of family caregivers of stroke patients - Farzaneh Edrisi; Shahram Etemadifar; Reza Masoudi; Morteza Sedehi; Nahid Jivad (Shahrekord University of Medical Sciences, 2021)
Background and aims: Stroke is the first leading cause of disability in adults. Long-term disability after stroke necessitates long-term caregiving by family members. The family caregivers (FCGs) of patients with stroke (PWS) experience different problems and hence, require self-management (SM) skills. The aim of this study was to assess the effects of an SM program based on Strauss and Corbin's SM model on perceived social support (PSS) among the FCGs of PWS. Methods: This quasi-experimental study was conducted in 2019-2020. Participants were eighty FCGs of PWS who were hospitalized in Kashani hospital, Shahrekord, Iran. They were purposefully- recruited and randomly allocated to a control and an intervention group. An SM program based on Strauss and Corbin's SM model was implemented in six ninety-minute sessions for participants in the intervention group. The Multidimensional Scale of PSS was used for PSS assessment before, immediately after, and two months after the intervention. Data were analyzed using the SPSS software (v. 16.0). Results: There was no significant difference between the groups in terms of the pretest mean score of PSS (P=0.76), while the mean score of PSS in the intervention group was significantly greater than the control group at both posttests (P<0.05). Moreover, the mean score of PSS in the control group did not significantly change across the three measurement time points (P>0.05), but significantly increased in the intervention group (P<0.05). Conclusion: SM program based on Strauss and Corbin's SM model is effective in significantly improving PSS among the FCGs of PWS. Therefore, nurses and other healthcare providers can use this program for the FCGs of PWS.